Mapping of Terraced Gardens through Geographic Information System (The Case Study of Armenian Culture) - Gabrielyan, Rafik; Ananyan , Artyom (History and Culture, 2025)
The article presents the spatial characteristics and distribution of terrace gardens in the Armenian Highlands and surrounding areas using Geographic Information Systems (GIS). The application of it method allows not only for the mapping of terrace gardens but also for uncovering their zonal distribution based on sea level and landscape features through spatial analyses.One of the traditional methods of land development and use is the formation of agricultural terrace systems, which is characteristic of many Armenian settlements. The creation of terrace systems helped protect sloping cultivated lands from soil erosion. In this regard, the geographical environment becomes the primary factor responsible for the creation of terraces. The article also addresses the principles, methods, and challenges of terracing, emphasizing the interconnection between terrace gardens and the landscape.
Keywords: Terraced Garden; Armenian Culture; Geographic Information System; Cartography; Topography; Ethnography; Landscape